Immediate removal of an entrapped central venous catheter guide wire - Bruthans, Jan; Trča, Stanislav (Prague Medical Report, 2019)
Extravasal guide wire entrapment due to fraying during central venous catheter placement using the Seldinger technique is a rare complication, which should be resolved as soon as possible. A 68-year-old male was scheduled for open right-side decortication. After the induction of general anesthesia, an attempt was made to place a central venous line in the right subclavian vein. However, the guide wire was entrapped extravasally between the right clavicle and the first rib. The exact site was located by palpating the bend of the guide wire in the subclavian triangle and the thoracic surgeon was available. Therefore, it was decided not to try to visualize the guide wire any further and to immediately proceed with surgical removal of the guide wire. The platysma muscle was dissected allowing access to the subclavian triangle. Venotomy of the external jugular vein was performed and the entrapped guide wire was removed via the venotomy. The whole complication was resolved within 30 minutes and the primary procedure was then performed. Managing rare complications of central venous line placement requires skill, ingenuity and, sometimes, interdisciplinary cooperation, either with a radiologist or a surgeon. The decision to proceed with immediate surgical removal of the guide wire proved a right one, and, to the best of our knowledge, such a strategy has not been described in the relevant literature to date.
Keywords: venae jugulares; Catheterization, Central Venous; katetrizace centrálních vén; Jugular Veins; lidé; senioři; mužské pohlaví; vena subclavia; Device Removal; Male; Aged; Central Venous Catheters; Subclavian Vein; odstranění implantátu; centrální žilní katétry; Humans